Interregional Rail Travelers' Assessment of Station Location, Services Provided and Access - Persson, Cristina Prather (Proceedings from the Annual Transport Conference at Aalborg University, 1996)
In 1988 the former Swedish State Railways was parted into two; the Swedish National Rail Administration, responsible for operation, maintenance and construction of the national rail network and The Swedish State Railways (SJ), responsible for traffic, stations and traffic operation and control. To increase and revitalise railway research, which during the last decades had been in decline, SJ initiated a sponsor programme for railway research. My research, which will conclude in a Ph.D.-dissertation summer ‘97, is financed by this sponsorship as well as by the Swedish Transportation and Communication Research Board (KFB). This paper is a brief presentation of my research.